PENGARUH BIMBINGAN ORANGTUA TERHADAP PRESTASI BELAJAR IPA SISWA KELAS VI SDN 004 BONTANG - Uminingsih Uminingsih (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study is intended to see the role of parental guidance to improve students’ achievement in IPA.  The study took place in the sixth grade students of SDN 004 Bontang Utara.  This study used correlational design. This study assigned 68 students as the respondents. Data of this study were collected from questionnaire and documents.  This study revealed that parental guidance significantly improves students’ achievement in IPA.  The higher the guidance is provided, the better the achievement in IPA the students gain.